Exchange-traded Funds, Investment Strategies, and Financial Stability - Michael Heinrich Baumann; Bernhard Herz; Michaela Baumann (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
Exchange-traded Funds (ETFs) are easy to understand, cost-efficient ways of investing in asset markets that have become very popular for both institutional and retail investors. The dynamics of the index and its underlying assets depend among others on the different types of traders in the market, price trends in individual stocks and the overall market, as well as over- or undervaluation of individual stocks and the index. Investing in an index of assets via an ETF can generate quite complex and sometimes counterintuitive investment behaviors on the level of individual assets. Seemingly stabilizing investment behavior on the level of the ETF might actually lead to destabilizing effects on the level of individual stocks.
Keywords: D01; G10; G11; 330; Exchange-traded index funds; ETF; index fund; financial stability; trading behavior